2021
DOI: 10.3390/cells10010083
|View full text |Cite
|
Sign up to set email alerts
|

Keap1-Nrf2 Pathway Regulates ALDH and Contributes to Radioresistance in Breast Cancer Stem Cells

Abstract: Tumor recurrence after radiotherapy due to the presence of breast cancer stem cells (BCSCs) is a clinical challenge, and the mechanism remains unclear. Low levels of ROS and enhanced antioxidant defenses are shown to contribute to increasing radioresistance. However, the role of Nrf2-Keap1-Bach1 signaling in the radioresistance of BCSCs remains elusive. Fractionated radiation increased the percentage of the ALDH-expressing subpopulation and their sphere formation ability, promoted mesenchymal-to-epithelial tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…Here, we reported the gene expression profiling of FACS-sorted MPM ALDH bright cells from an MPM representative cell line. This follows a series of observations made by others and us in several experimental settings, suggesting that the ALDH bright cells may mediate chemoresistance [ 22 , 33 , 40 , 41 ]. To date and to the best of our knowledge, a full gene expression profiling of FACS-sorted ALDH bright cells is unprecedented in MPM.…”
Section: Discussionsupporting
confidence: 81%
“…Here, we reported the gene expression profiling of FACS-sorted MPM ALDH bright cells from an MPM representative cell line. This follows a series of observations made by others and us in several experimental settings, suggesting that the ALDH bright cells may mediate chemoresistance [ 22 , 33 , 40 , 41 ]. To date and to the best of our knowledge, a full gene expression profiling of FACS-sorted ALDH bright cells is unprecedented in MPM.…”
Section: Discussionsupporting
confidence: 81%
“…In another investigation, the silencing of Nrf2 reduced the expression of ALDH1 in pancreatic cancer cells and promoted their sensitivity to the chemotherapeutic drug, 5-fluorouracil [48]. Furthermore, the Nrf2 pathway was reported to regulate ALDH1 and contribute to radioresistance in breast CSCs [49]. In the present study, luteolin reduced ALDH1 + breast cancer cells thorough the downregulation of Nrf2.…”
Section: Discussionsupporting
confidence: 64%
“…4E). Altogether, this indicated that exogenous administration of AA fully mimicked the cell subpopulation rearrangement and the gene expression changes that others and we have described in chemotherapy-treated MPM cell cultures [13,[43][44][45][46][47].…”
Section: Aa Increased the Expression Of Csc-and Emt-related Genessupporting
confidence: 72%